OPTIMIZATION OF THE USE OF TECHNOLOGY IN ENGLISH LEARNING BASED ON TPACK (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE) - Hadi Irawan, Doni; Khoiruman, Muhamad Alfi (Jurnal Review Pendidikan dan Pengajaran, 2025)
The optimization of technology in English learning based on the Technological Pedagogical Content Knowledge (TPACK) framework plays a crucial role in enhancing the effectiveness and engagement of language education. This study examines the implementation of TPACK-based technology in English learning, identifying both its benefits and challenges. The findings indicate that integrating digital tools, such as Learning Management Systems (LMS), interactive applications, and adaptive learning software, positively impacts learning quality by increasing accessibility, student motivation, and active participation. However, several obstacles persist, including limited technological infrastructure, insufficient lecturer competence, and a lack of interactive digital learning materials. To address these challenges, this study recommends targeted optimization strategies, including professional development programs for lecturers, improved technology infrastructure, the adoption of a Bring Your Own Device (BYOD) policy, and the development of engaging digital content. Furthermore, a differentiated learning approach utilizing adaptive technology is essential to accommodate students’ diverse learning preferences. The study highlights the need for continued research on the long-term effectiveness of TPACK-based technology integration and its impact on students' communication skills in English. By implementing these strategies, English learning can become more innovative, interactive, and aligned with modern educational demands.